Moderasi Beragama dalam Komunikasi Lintas Kultural di Pancur Batu - Hijrah Hayani; Nursapia Harahap (MUKASI: Jurnal Ilmu Komunikasi, 2025)
This study explores the practice of religious moderation within the dynamics of intercultural communication in Pancur Batu District, Deli Serdang Regency, North Sumatra a region known for its ethnic, religious, and cultural diversity. Employing a qualitative ethnographic approach, the research highlights how intercultural communication becomes a crucial instrument in sustaining social harmony amidst pluralism. The findings reveal that values of religious moderation such as respect for diversity, non violence, and recognition of local cultural wisdom are embedded through various socializing agents, including religious leaders, educational institutions, family structures, and traditional customs. Invisible cultural elements, such as empathy, tolerance, and mutual respect, serve as the foundation for daily social interactions. The study also underscores the vital role of the Interfaith Harmony Forum (FKUB) in facilitating dialogue and promoting peaceful coexistence among religious communities. Additionally, the strategic use of social media has expanded the dissemination of messages advocating tolerance and unity. These collaborative efforts contribute to a social environment where differences are not merely tolerated but embraced as a source of collective strength. In conclusion, the experience of Pancur Batu offers a valuable model for managing religious and cultural diversity, which can be adapted by other multiethnic and multireligious communities across Indonesia.